2022
DOI: 10.3389/fendo.2022.916951
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lipid risk score and new-onset hypertension in a prospective cohort study

Abstract: BackgroundDyslipidemia and hypertension are both important risk factors for atherosclerotic cardiovascular diseases. However, the relationship between dyslipidemia and incident hypertension remains to be elucidated comprehensively. The main purpose of this study was to construct the lipid risk score to explore the risk prediction effect of integrated lipid indices on new-onset hypertension.MethodsThis prospective cohort study with 2116 non-hypertensive subjects was conducted from 2009 to 2020. New hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Visceral adiposity index (VAI) and waist/height ratio (WHtR) [20,40]. Similarly, the present study also showed that LAP (AUC = 0.66) has higher diagnostic value than WC (AUC = 0.60) and TG (AUC = 0.64).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Visceral adiposity index (VAI) and waist/height ratio (WHtR) [20,40]. Similarly, the present study also showed that LAP (AUC = 0.66) has higher diagnostic value than WC (AUC = 0.60) and TG (AUC = 0.64).…”
Section: Discussionsupporting
confidence: 74%
“…The association between LAP and T2DM has been found to be positive in several demographic and ethnic subgroups. Brie y, in the Japanese population, high LAP have been shown to increase the risk of T2DM by 76% over time [20]. Similar results have been reported in adults Chinese and middle-aged Koreans [27,28].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…According to the study by Sesso et al, the baseline lipid levels, especially HDL-C and non-HDL-C, and the TC/HDL-C ratio are associated with an increased risk of hypertension [9]. In the prevention and control of hypertension, attention should be paid to the control of lipid metabolism [35].…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomics is widely used in biomedical research, especially in evaluating the lipid metabolism status of diseases (Yang & Han, 2016). As compared to traditional lipidomics, the application of diurnal lipidomics not only reflects the changes in metabolites in diffident groups in vivo but also comprehensively characterizes the 24-h changes in metabolites in vivo (Xie et al, 2022). Lipid circadian rhythm fluctuation is a normal physiological phenomenon, showing the differences in circadian metabolic activity (Poggiogalle et al, 2018).…”
Section: Discussionmentioning
confidence: 99%